2020
DOI: 10.2298/vetgl200527008s
|View full text |Cite
|
Sign up to set email alerts
|

Borellia burgdorferi infection in removed ticks and anti-borrelia antibodies in infested patients admitted to the Pasteur institute, Novi Sad

Abstract: Introduction. The primary objectives of this study were (1) to determine the presence of Borrelia burgdorferi infection in ticks removed from patients for the purpose of singling out sites with increased risk of Lyme borreliosis, and (2) to determine the presence of IgM and/or IgG antibodies against B. burgdorferi sensu lato (s. l.) complex in sera of patients who had ticks removed. Materials and Methods. From 108 ticks removed from patients, all were examined zoologically and a sub-sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…complex ( Sykes and Makiello, 2017 ). When the overall Borrelia prevalence found in the present study is compared to results of other similar studies in Serbia, we see wide variations between localities, ranging from 10 to 40.7% ( Simin et al, 2020 ; Banovic et al, 2021b ; Stosic et al, 2021 ). Compared to neighboring countries of Serbia, the Borrelia prevalence in ticks found in our study is higher compared to that of Croatia ( Tadin et al, 2016 ), Bulgaria ( Nader et al, 2018 ), and Romania ( Kalmar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…complex ( Sykes and Makiello, 2017 ). When the overall Borrelia prevalence found in the present study is compared to results of other similar studies in Serbia, we see wide variations between localities, ranging from 10 to 40.7% ( Simin et al, 2020 ; Banovic et al, 2021b ; Stosic et al, 2021 ). Compared to neighboring countries of Serbia, the Borrelia prevalence in ticks found in our study is higher compared to that of Croatia ( Tadin et al, 2016 ), Bulgaria ( Nader et al, 2018 ), and Romania ( Kalmar et al, 2020 ).…”
Section: Discussionsupporting
confidence: 68%
“…I. ricinus was the predominant tick species found in the study, accounting for 117 out of 121 (96.69%) specimens. This finding was expected since I. ricinus is the main tick vector for the TBE virus in Western Europe [ 35 ], and the most widespread tick species in Serbia [ 36 , 37 , 38 ]. All active developmental stages of I. ricinus , including larvae, nymphs, and adults, can be infected with TBEV and transmit the virus, throughout the whole life cycle to animal reservoirs and humans [ 39 ].…”
Section: Discussionmentioning
confidence: 79%
“…Tick species identified on dogs in this study had previously been identified on domestic dogs in the Vojvodina region, in which I. ricinus and R. sanguineus were the most prevalent tick species [ 19 ]. I. ricinus and R. sanguineus are among the most common ectoparasites found infesting dogs and goats in Serbia, as well as in other countries in the Balkans such as North Macedonia, Montenegro, Romania and, Bosnia and Hercegovina [ [20] , [21] , [22] , [23] ]. Infestations with R. sanguineus in houses is frequently reported in the literature [ [24] , [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, B. burgdorferi s.l. have been identified in competent vectors of the genus Ixodes , mainly I. ricinus , as well as in human serum samples [ 23 , 39 ]. The risk factors associated with human infection by Borrelia includes the presence and abundance of competent tick vectors in different types of habitats, a high prevalence of B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%